PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER BANGSA (Studi Analisis Perilaku Siswa Madrasah Aliyah Negeri 1 Palembang) - Muhajir Syarif (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2014)
AbstractThis study aims to determine how Islamic religious education in shaping the character of the nation. How a student's character in MAN 1 Palembang, and how the behavior of students in Madrasah Aliyah Negeri 1 Palembang. The research in this thesis using mixed methods research approaches that use both quantitative and qualitative approaches in the study in order to understand the research problem. The technique of collecting data are: observation, documentation, and questionnaires. While the analysis of the data were analyzed in two ways, namely qualitative and quantitative way. The processing of quantitative data using descriptive statistics and using SPSS, whereas qualitative data through three flow of activities: data reduction, data presentation and data verification / conclusion.Based on the findings in the field that I did it through observation to school in Madrasah Aliyah Islamic education in shaping the character has an important role and the efforts that are systematically designed and implemented to help students understand the values of human behavior which manifested itself in the mind, attitude , feelings, words, and actions based on religious norms.From the analysis of the data in this thesis found First, Islamic Education in the formation of national character is through the subject matter PAI later developed in everyday student at school. Character formation systematically implemented to help students understand the values and character of human behavior associated with gods, themselves, fellow humans, the environment, and manners, which supported the establishment of a character appropriate method in coaching youth Islamically. Second, students in the formation of character MAN 1 Palembang is to unify the value contained in the material character PAI later developed in students' everyday personal forming students who adhere to religion and the State. In this case seen from the answers questionnaire distributed to 100 students were included in both categories by 81%, pretty good by 15% and 4% poor. Third, the behavior of students in Madrasah Aliyah Negeri 1 Palembang classified in the category of good, polite, well-mannered, respectful to teachers and to worship and obey the school rules. It is seen from the answer to a questionnaire distributed to 100 students were included in both categories by 79%, pretty good by 12% and 10% unfavorable. Keywords: PAI Education, Character nation, Student Behavior.